Bentuk Afiks dan Proses Morfofonemik Bahasa Batak Angkola - Aisah Amini, Khofifah; Nadra, Nadra; Marnita, Rina (GERAM: Gerakan Aktif Menulis, 2023)
The Batak Angkola language is one of the regional languages used by the Angkola people in Batang Angkola District, South Tapanuli Regency. This study aims to describe the affix forms and morphophonemic processes of the Batak Angkola language. The type of study is descriptive research with a qualitative approach. The data in this study are affixed words spoken by three informants from Pintu Padang Village, Batang Angkola District, South Tapanuli Regency. The methods used in data collection are observation and interview methods. Observations were made by listening to speakers of the Batak Angkola language when communicating with each other. The results of the listening are tapped using notes or also known as tapping techniques and note-taking techniques. The interview method was carried out by asking directly the informants who had been selected based on predetermined requirements. Based on the results of the study, it was shown that the forms of affixes in the Batak Angkola language are (1) prefixes in the form of ma(N)-, pa(N)-, mar-, tar-, par- and marsi-; (2) suffixes are –kon, -an, and –i; (3) confixes are ma(N)-i, ma(N)-on, pa(N)-kon, mar-an, tar-on, marsi-an, pa(N)-an, and i-kon. The morphophonemic process found are (1) the process of phoneme appearance; (2) phoneme melting; (3) phoneme deletion; (4) phoneme changes; (5) phoneme change, dissolution, and appearance; and (6) phoneme deletion and change.